PREDICTIVE VALUE OF D-DIMER FOR THROMBOSIS, DISEASE STAGE, AND METASTASIS IN CANCER PATIENTS ACROSS ORGAN SYSTEMS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the value of D-dimer in predicting thrombosis, disease stage and metastasis across cancer organ systems.Subjects and methods: A descriptive, cross-sectional analytical study on 557 cancer patients who underwent D-dimer testing from January 2024 to January 2026. Diagnostic value was assessed using ROC curves and area under the curve (AUC).Results: The majority of patients were diagnosed at a late stage, particularly esophageal (97.14%), gastric (93.1%) and lung cancer (91.26%). Metastasis rates were highest in respiratory (70.48%), digestive (61.8%) and reproductive cancers (60.27%). The overall thrombosis rate was 14%, highest in renal-urinary (22.22%), digestive (21.35%). D-dimer was elevated in most cancer groups and significantly higher in patients with thrombosis. D-dimer showed the best predictive value in reproductive cancers (AUC for late stage = 0.8147; thrombosis = 0.7104), followed by respiratory cancers, moderate in digestive cancers and lowest in head and neck cancers.Conclusion: D-dimer has predictive value for thrombosis and disease progression in cancer patients, particularly in reproductive cancers. Predictive performance varies across organ systems, suggesting a potential role for individualized use of D-dimer in risk assessment and monitoring of cancer patients.